A Review of the Ethnopharmacology, Phytochemistry, Pharmacology, Application, Quality Control, Processing, Toxicology, and Pharmacokinetics of the Dried Rhizome of Atractylodes macrocephala - Yang, Liu; Yu, Huan; Hou, Ajiao; Man, Wenjing; Wang, Song; Zhang, Jiaxu; Wang, Xuejiao; Zheng, Senwang; Jiang, Hai; Kuang, Haixue (Frontiers in Pharmacology, 2021)
This product is the dried rhizome of Atractylodes macrocephala Koidz, which is also known as Dong Bai Zhu, Wu Zhu, Yu Zhu, etc. It has the effect of invigorating spleen and replenishing qi, clearing damp and diuresis, hidroschesis and fetal safety. It is often used for the treatment of diseases such as spleen deficiency and less food, abdominal distension and diarrhea, sputum, vertigo, edema, fever and sweating, and a small amount of vaginal bleeding during pregnancy. In this paper, the botany, ethnopharmacology, application, phytochemistry, analytical methods, quality control, processing, pharmacology, toxicology and pharmacokinetics of Atractylodis Macrocephalae Rhizoma (AMR) in China in the past 30 years were reviewed. The relevant information and data of AMR were collected from CNKI, VIP, PubMed, Web of Science, scientific database, Chinese medicinal material encyclopedia, Chinese herbal medicine classics, Chinese medicine dictionary, doctor's and master's thesis, and so on. AMR has diuretic effect, anti-diuretic effect, anti-inflammatory, antitumor function, regulate gastrointestinal function, and the roles of anticoagulant, improve the nervous system disease, affect the immune system, regulate uterine smooth muscle, anti-oxidation, anti-aging, antibacterial, hypoglycemic effect, analgesic action, on the liver ischemia-reperfusion injury (IRI) in rats of protection, inhibition of aromatase, treatment of bone disease, strengthening myocardial contraction ability, detoxification and cholagogic effect, fall hematic fat action, such as the treatment of acute renal injury and so on. Sesquiterpenoids, triterpenoids, Polyacetylenes, phenylpropanoids, Coumarins, flavonoids, Flavonoid glycosides, steroids, benzoquinones, Polysaccharides and other compounds were isolated from AMR. Among them, Sesquiterpenoids, Polysaccharides and Polyacetylenes are the main components of AMR. AMR has a wide range of pharmacological effects, and has a large proportion in the composition of many proprietary Chinese medicines. Meanwhile, it mainly affects the endocrine system, nervous system and urinary system. These important informations suggest that we should focus on the development of new drugs related to AMR, including some specific components in AMR, so that AMR can play a greater therapeutic potential and further explore the information related to AMR. At the same time, attention should be paid to the rational use of AMR resources to avoid the shortage of resources caused by excessive harvesting.